Study protocol on comparative effectiveness of mindfulness meditation and qigong on psychophysiological outcomes for patients with colorectal cancer: a randomized controlled trial - Rainbow T. H. Ho; Adrian H. Y. Wan; Jessie S. M. Chan; S. M. Ng; K. F. Chung; Cecilia L. W. Chan (BMC, 2017)
Abstract Background Colorectal cancer imposes threats to patients' well-being. Although most physical symptoms can be managed by medication, psychosocial stressors may complicate survival and hamper quality of life. Mindfulness and Qigong, two kinds of mind-body exercise rooted in Eastern health philosophy, has been found effective in symptoms management, improving mental health, and reducing stress. With these potential benefits, a randomized controlled trial (RCT) is planned to investigate the comparative effectiveness of mindfulness and Baduanjin intervention on the bio-psychosocial wellbeing of people with colorectal cancer. Methods/ design A 3-arm RCT with waitlist control design will be used in this study. One hundred eighty-nine participants will be randomized into (i) Mindfulness, (ii) Baduanjin, or (iii) waitlist control groups. Participants in both the Baduanjin and mindfulness groups will receive 8-weeks of specific intervention. All three groups will undergo four assessment phases: (i) at baseline, (ii) at 4-week, (iii) at 8-week (post-intervention), and 6-month post-intervention (maintenance). All participants will be assessed in terms of cancer-related symptoms and symptom distress, mental health status, quality of life, stress level based on physiological marker. Discussion Based on prior research studies, participants in both the mindfulness and Baduanjn intervention group are expected to have better symptoms management, lower stress level, better mental health, and higher level of quality of life than the control group. This study contributes to better understanding on the common and unique effectiveness of mindfulness and Baduanjin qigong, as such patients and qualified healthcare professionals can select or provide practices which will produce maximum benefits, satisfaction, adherence, and sustainability. Trial registration The trial has been registered in the Clinical Trials Centre of the University of Hong Kong ( HKCTR-2198 ) on 08 March 2017.